Estimation of Time Series Databases Performance in Cloud Applications for Plastic Moulding Industry - Veligorskyi, Oleksandr; Chakirov, Roustiam; Khomenko, Maksym (2024 International Conference on Electrical, Computer and Energy Technologies (ICECET, 2024)
This paper describes the approach for performance estimation of data queries in time series databases, implemented for the remote monitoring and control of injection plastic moulding systems. Experimental setup, structure of InfluxDB database and queries has described. Field experiments of data retrieving have been used to analyse the execution time for the queries as a function of query parameters. The influence of the time interval for the number of output points in query, averaging time and number of channels on time costs has been established. It was shown, that query execution time can be estimated by means of linear function of query parameters.